Determination of sulfamide residues in guinea pig carcasses in sale in the Mantaro Valley, Junín, Peru - Champi C., María Fernanda (2022)
The present study aimed to determine the presence of sulfomide residues that exceed the maximum residue limits in guinea pig carcasses in sale in the Mantaro Valley, Junín, Peru, in 2020. In total, liver, muscle and kidney samples were evaluated from 433 guinea pig carcasses. The detection of antibiotic residues was carried out by the agar diffusion technique, resulting 62.6 ± 4.5% (271/433) posive samples in kidney, 59.4 ± 4.6% (257/433) in liver and 31.4 ± 4.3% (136/433) in muscle. Moreover, 82 positive samples with the highest inhibition halos were taken for analysis using a commercial ELISA kit specific for sulfonamides (MaxSignal® Sulfonamide ELISATest Kit), obtaining 4.9 ± 4.6% (4/82) of samples with concentrations greater than 100 µg/kg. The results showed the presence of sulfonamide residues in concentrations that exceed the maximum limits of residues allowed in guinea pig carcasses in sale in the Mantaro Valley, Junín.